SURVEY ON DYNAMIC DATA SHARING IN PUBLIC CLOUD USING MULTI-AUTHORITY SYSTEM - Priyanka Phasale .; Priyanka Kokate; Prof M.C. Kshirsagar (International Journal of Innovations in Engineering Research and Technology, 2021)
The continuous development of cloud computing, several trends are opening up to new forms of outsourcing. Public data integrity auditing is not secure and efficient for shared dynamic data. In existing scheme figure out the collusion attack and provide an efficient public integrity auditing scheme, with the help of secure group user revocation based on vector commitment and verifier–local revocation group signature. It provides secure and efficient scheme which support public checking and efficient user revocation. Problem of existing work they used TPA (Third party auditor) for key generation and key agreement. Use of TPA as central system if it fails then whole system gets failed. If we are working with cloud, user identity is major concern because user doesn’t want to reveal his personal information to public. This concept not included in it. In this paper, based these con’s we proposed a dynamic data sharing in public cloud using multi-authority system. The proposed scheme is able to protect user’s privacy against each single authority.